2019
DOI: 10.1148/radiol.2019190420
|View full text |Cite
|
Sign up to set email alerts
|

Hyperpolarized Helium 3 MRI in Mild-to-Moderate Asthma: Prediction of Postbronchodilator Reversibility

Abstract: Background: Longitudinal progression to irreversible airflow limitation occurs in approximately 10% of patients with asthma, but it is difficult to identify patients who are at risk for this transition. Purpose: To investigate 6-year longitudinal changes in hyperpolarized helium 3 (3 He) MRI ventilation defects in study participants with mild-to-moderate asthma and identify predictors of longitudinal changes in postbronchodilator forced expiratory volume in 1 second (FEV 1) reversibility Materials and Methods:… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
27
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(27 citation statements)
references
References 35 publications
0
27
0
Order By: Relevance
“…In spontaneous breathing, standard spirometry loses all sensitivity to ventilation defects and any disease specificity as the global flow-volume loops are generally affected only when the lung is challenged to the limit of its abilities. Even at the high and low pressures that are reached during coached forced breathing, FVC and FEV 1 may fail revealing or staging lung dysfunction as it was brought to light early on by hyperpolarized gas MRI when the recorded percentage of ventilation defects did not always correlate with standard spirometry [20][21][22][23] . In 3D MR Spirometry, because of the long total scan time, only spontaneous breathing can be reasonably performed by the patient.…”
Section: Discussionmentioning
confidence: 99%
“…In spontaneous breathing, standard spirometry loses all sensitivity to ventilation defects and any disease specificity as the global flow-volume loops are generally affected only when the lung is challenged to the limit of its abilities. Even at the high and low pressures that are reached during coached forced breathing, FVC and FEV 1 may fail revealing or staging lung dysfunction as it was brought to light early on by hyperpolarized gas MRI when the recorded percentage of ventilation defects did not always correlate with standard spirometry [20][21][22][23] . In 3D MR Spirometry, because of the long total scan time, only spontaneous breathing can be reasonably performed by the patient.…”
Section: Discussionmentioning
confidence: 99%
“…It has been shown that the presence of ventilation defects, frequently observed in patients with asthma, is due to heterogeneous airway closure or narrowing of small airways [145]. In several studies it was shown that ventilation defects are not seen randomly but they might be predefined [146] or a result of remodelling [147]. Furthermore, it has been shown that ventilation defects persist over time [146,148,149].…”
Section: Dynamic Imagingmentioning
confidence: 99%
“…Therefore, some sort of partial or intermittent closure must be present in the patients with persisting ventilation defects or these areas are ventilated through collateral ventilation [150]. Ventilation defects are associated with disease severity [144,147,151,152], lung clearance index [152] and spirometry [144,151].…”
Section: Dynamic Imagingmentioning
confidence: 99%
“…
The underlying pathophysiological determinants of asthma and COPD are related in complex ways. Importantly however, post-bronchodilator forced expiratory volume in 1 s (FEV 1 ) reversibility may occur in approximately 50% of COPD patients [1], whilst epidemiological [2] and magnetic resonance imaging (MRI) studies [3] suggest that, in asthma patients, FEV 1 reversibility may diminish over time. As compared to patients with asthma or COPD alone, patients with co-existing asthma and COPD report worse clinical outcomes [4] and increased healthcare costs [5] and burden [4,5].Hyperpolarised 3 He and 129 Xe MRI studies have reported clinically relevant post-bronchodilator improvements in MRI ventilation defects in patients with asthma [6] and COPD [7], independent of FEV 1 reversibility.
…”
mentioning
confidence: 99%
“…To better understand bronchodilator reversibility in patients with a diagnosis of asthma or COPD, we retrospectively evaluated spirometry and hyperpolarised 3 He MRI measurements in participants with asthma (age ⩾40 years, <1 pack-year smoking history) and COPD (age 60-85 years, >10 pack-years smoking history). We expected that MRI would detect post-bronchodilator reversibility in participants in whom there was negligible post-bronchodilator FEV 1 reversibility, thereby providing a small and large airway quantitative functional measurement with more enhanced sensitivity to small airways disease and greater dynamic range than FEV 1 .…”
mentioning
confidence: 99%